Kelangsungan dan Perlawanan Politik Identitas dalam Bingkai Keadaban Demokrasi - Zuly Qodir; Syahbuddin Latief (Jurnal Studi Pemerintahan, 2011)
This paper is about the sustainability of photographing pelawanan identity politics carried out by civil society in the construction of a civilized democracy. This paper shows that the people in his own way to fight against state policies that are considered political guarantees of political freedoms has occurred despite the 1998 reform. This paper is based on three case study villages in the Java community resistance, the imposition of Islamic sharia movement in the NAD and the Liberal Islam movement. The writing in this article uses the perspective of identity politics approach to democracy and civilization which presupposes the existence of freedom and public participation. The data, carried out by the method of interviews, documentation and discussion focused.